Kinetics of the Oxidative Dehydrogenation of Polyamines in Iron Coordination Compounds. - López Taco, Iván Augusto (2020)
The reactivity of the oxidative dehydrogenation (OD) reactions is influenced by the coordination of the ligands to transition metals. Such oxidative dehydrogenation reactions have been studied for a long time due to their broad participation in chemical and biological systems, and their potential application in the industrial sector, as batteries and alternative energy sources to fossil fuels. Some works on the reaction mechanisms including the activity of molecular oxygen during the reaction process, have been reported before. However some details on these mechanisms and the influence of external oxidants have not yet been fully understood, so further investigation is needed. In the present work, in an attempt to contribute in somehow to increase the knowledge to the mechanism behind this type of reactions, the synthesis, characterization and results of the study of two oxidative dehydrogenation reactions under oxygen atmosphere (air) are presented. In particular, we worked with two systems composed of two different dipyridinic ligands and a [Fe(DMSO)6](NO3)3 complex as the iron source. Both dipyridinic ligands are differentiated only by the position of the substitution in the pyridine rings. Despite the slightly difference between the ligands, it was found that the OD reaction occurs only in one system, this was verified by UV-Vis analysis and by cyclic voltammetry studies of the reaction products between the two ligands with the iron complex. Even more, it was found that the difference in the substitution of the pyridine rings generates a great change in the pKa values for each ligand, which is crucial for the development or not of the oxidative dehydrogenation. Thus, rate constants of different order of magnitude were found for both reactions. This was attributed to the fact that in the system in which OD does not occur, the constant is only influenced by the coordination of the ligand to the transition metal, while for the second system the constant is influenced both by the coordination of the ligand to the metal as well as by the OD process. Finally, the results obtained together with the bibliographic study allowed us to suggest a reaction mechanism for both systems.